Exploring the Development of Social Intelligence of Students During University Years - Mushtaq Ahmad Malik, Faisal Siddique, Syed Nasir Hussain, (PJE, 2023)
During university years students go through educational as well as social interactions and achieve manifold developments. The purpose of the study was to explore the development of social intelligence during university years among University students. The study was delimited to four year under graduate programs Bachelor of Science (BS) students of University of Sargodha. The cross-sectional study includes the students of BS programs 1st semester and 7th semester. Using multi-stage sampling technique, 560 students in total from seven department of the university were selected as the sample. Tromso Social Intelligence Scale (TSIS) with reliability coefficient (Cronbach Alpha) 0.75 was used. It was found that overall the development of social intelligence during university years was at good rate and statistically significant. The urban and rural backgrounds students and boarder and day scholar students reported equal level of social intelligence; whereas male students reported higher level of social intelligence than the female students. It is recommended that the universities may arrange seminars and group discussion to provide social interaction to students. University administration and teachers may arrange co-curricular activities and other social gatherings at inter-departmental and inter-university level.